2012
DOI: 10.1016/j.yexcr.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid influence on platelet-induced airway smooth muscle cell proliferation

Abstract: Hyaluronic acid (HA) is one of the main components of the extracellular matrix (ECM) and is expressed throughout the body including the lung and mostly in areas surrounding proliferating and migrating cells. Furthermore, platelets have been implicated as important players in the airway remodeling process, e.g. due to their ability to induce airway smooth muscle cell (ASMC) proliferation. The aim of the present study was to investigate the role of HA, the HA-binding surface receptor CD44 and focal adhesion kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…As a polysaccharide, HA has the potential to develop heparin‐induced thrombocytopenia, and an increased serum level of HA has been correlated with low platelets syndrome . It has been reported that CD44 is expressed on the surface of platelets, and it has previously been shown that platelets can bind to HA via surface‐expressed CD44 . Besides, CD44 is also expressed on circulating lymphocytes but does not bind to HA before receptor deglycosylation .…”
Section: Resultsmentioning
confidence: 99%
“…As a polysaccharide, HA has the potential to develop heparin‐induced thrombocytopenia, and an increased serum level of HA has been correlated with low platelets syndrome . It has been reported that CD44 is expressed on the surface of platelets, and it has previously been shown that platelets can bind to HA via surface‐expressed CD44 . Besides, CD44 is also expressed on circulating lymphocytes but does not bind to HA before receptor deglycosylation .…”
Section: Resultsmentioning
confidence: 99%
“…As the main components of the extracellular matrix, HA and proteins play an important role in tissue regeneration and repair. This biomimetic hydrogels has been used for research or application of brain [ 57 , 79 ], liver [ 80 ], muscle [ 81 , 82 ], skin [ 58 ] and cartilage [ 17 , 83 ] tissue engineering. Therefore, in addition to the permeability, HA and GEL in TSHSP bioink also contributed to the remarkable biological specificities of in vitro tissue-like constructs.…”
Section: Discussionmentioning
confidence: 99%
“…2 In this study, downregulation of ARHGAP26 expression caused a decreased proliferation rate and ability of human DASMC to migrate, both of which are closely correlated with structural closure of human DA. HAS2, a key enzyme for HA production in mammalian cells and HA, which has been reported to be closely related to cell proliferation, adhesion, and migration, 19 were both reduced after downregulation of ARHGAP26 in human DASMCs in vitro. Yokoyama et al 20 pointed that when HA production was inhibited, the migration of DASMCs was negated.…”
Section: Arhgap26 Deficiency Inhibits the Proliferation And Migration...mentioning
confidence: 95%